2013
DOI: 10.4161/auto.25831
|View full text |Cite
|
Sign up to set email alerts
|

A conserved domain in exon 2 coding for the human and murine ARF tumor suppressor protein is required for autophagy induction

Abstract: The ARF tumor suppressor, encoded by the CDKN2A gene, has a well-defined role regulating TP53 stability; this activity maps to exon 1β of CDKN2A. In contrast, little is known about the function(s) of exon 2 of ARF, which contains the majority of mutations in human cancer. In addition to controlling TP53 stability, ARF also has a role in the induction of autophagy. However, whether the principal molecule involved is full-length ARF, or a small molecular weight variant called smARF, has been controversial. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
(65 reference statements)
3
46
1
Order By: Relevance
“…In contrast, more aggressive type II serous tumors showed a dramatic mRNA increase of an autophagy inducer, CDKN2A ( Table 2; Table S5), previously reported to distinguish serous from endometrioid carcinomas by high protein expression 13,44 and to be associated with migration and invasion. 45 Both protein products of CDKN2A (ARF and INK4a) induce autophagy 46,47 and a recent IHC analysis of 360 UCEC patient samples shows higher counts of MAP1LC3A/LC3A 'stone-like structures' that are associated with poor prognosis subtypes, 48 including: serous papillary, clear cell, and high-grade endometrioid. Further study of the autophagy status of less aggressive type I endometrioid tumors compared to more aggressive type II serous tumors may reveal a role for autophagy in the pathogenesis of endometrial carcinomas.…”
mentioning
confidence: 99%
“…In contrast, more aggressive type II serous tumors showed a dramatic mRNA increase of an autophagy inducer, CDKN2A ( Table 2; Table S5), previously reported to distinguish serous from endometrioid carcinomas by high protein expression 13,44 and to be associated with migration and invasion. 45 Both protein products of CDKN2A (ARF and INK4a) induce autophagy 46,47 and a recent IHC analysis of 360 UCEC patient samples shows higher counts of MAP1LC3A/LC3A 'stone-like structures' that are associated with poor prognosis subtypes, 48 including: serous papillary, clear cell, and high-grade endometrioid. Further study of the autophagy status of less aggressive type I endometrioid tumors compared to more aggressive type II serous tumors may reveal a role for autophagy in the pathogenesis of endometrial carcinomas.…”
mentioning
confidence: 99%
“…Another similarity we found between ARF and BCL-xL-interacting BH3-only proteins was a second BCL-xL-binding site in the C terminus. This region in ARF comprises an evolutionary conserved sequence important for mitochondrial localization of ARF, but consistent with the presence of two BCL-xL-binding sites, mutations in this region were unable to abrogate the interaction between ARF and BCL-xL 53 .…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have shown that ARF can localize to mitochondria when overexpressed in transformed cells, and a number of mitochondrial interaction partners for ARF have been identified 10,27,38,53 . In various cellular model systems, ARF interacts with p32 and induces mitochondrial membrane depolarization, leading to apoptotic or autophagic cell death responses 38,54 .…”
Section: Discussionmentioning
confidence: 99%
“…MEFs expressing smArf alone, like Arf-null MEFs (2), adapted a spindle-shaped morphology, lost contact inhibition, and overgrew one another following KRas transduction, implying that they were defective in tumor suppression (see below). Enforced vector-mediated overexpression of smArf has been reported to reduce mitochondrial membrane potential and to trigger selective autophagy (mitophagy) (16,18) through mechanisms that do not trigger cytochrome c release or loss of ATP production, and that depend on direct binding to the matrix protein p32 (gC1qR, C1QBP) (21) and on the autophagy regulators ATG5 and Beclin-1 (14), PINK1, and Parkin (22). Unlike p19 Arf which is directed to the nucleolus and stabilized by NPM, the endogenously produced smArf protein is imported into mitochondria (Figs.…”
Section: Mitochondrial Localization Of the Endogenously Produced Smarfmentioning
confidence: 99%
“…The single ORFs of the mouse (Arf) and human (ARF) mRNAs contain two, and only two, AUG codons (encoded by exon-1β) that specify methionines (M)-1 and -45 of p19 Arf (M48 in human p14 ARF ), each of which can initiate translation (14). The N-terminally truncated protein, p15 smArf , initiated at M45 is highly unstable (14), lacks amino acid residues required for p53 activation and NPM binding (15), localizes to mitochondria (14), and has been reported to trigger autophagy and/or mitophagy when overexpressed (16)(17)(18). By generating mice that produce either p15 smArf or full-length p19 Arf alone, we have now elucidated distinct physiological roles played by the two Arf proteins.…”
mentioning
confidence: 99%